Does company size and profitability affect corporate social responsibility disclosure? - Rukaanisy Syahierah; Ashilla Larasati (Faculty of Business & Economics, Universitas Islam Indonesia, 2019)
Purpose: This research is aimed to analyze whether disclosure of corporate social responsibility (CSR) of sharia bank in Indonesia is influenced by some factors.Methodology: This research used the data from Islamic Social Reporting (ISR) index. ISR was evaluated based on content analysis; that is by analyzing annual report of 11 sharia banks.Findings: Multiple regressions showed that company size significantly affected the level of disclosure of CSR but it was the contrary for profitability.Originality/contributions: This is the first study to used 11 sharia banks in Indonesia during the period of 2010-2013.